Proposed Improvement of Production Facility Layout at PT XYZ Using Activity Relationship Chart (ARC) Method to Minimize Material Handling Costs - Widia, Iis; Bhagya, Tombak Gapura; Anggaliya, Pipin (Sainteks: Jurnal Sain dan Teknik, 2025)
PT XYZ is a company engaged in the production of herbal food products. Observations indicate that the current production facility layout is not optimal, primarily due to the use of two separate buildings, which results in inefficient material flow. The presence of backtracking patterns and underutilized areas further contributes to increased material handling costs, which reach Rp5,846,182 per month. This study aims to propose an improved facility layout to minimize material transfer distance and time while reducing material handling costs, thereby enhancing production efficiency. The Activity Relationship Chart (ARC) method is employed to analyze the interrelationships between production activities based on spatial proximity. Data were collected through questionnaires distributed to production employees to identify layout requirements for greater efficiency. The ARC analysis results are visualized in the Activity Relationship Diagram (ARD) and Area Allocation Diagram (AAD), which serve as the foundation for designing the proposed layout. The evaluation of the new layout demonstrates significant improvements, including a reduction in material transfer distance by 31,999 meters per month, a decrease in transfer time by 17,480 seconds per month, and an efficiency gain in material handling costs amounting to Rp3,522,508 per month (60.25%). These findings are expected to serve as a reference for the manufacturing sector in designing more efficient production facility layouts to enhance productivity and reduce operational costs.